CLASSROOM TEACHING MANAGEMENT AND EVALUATIVE TECHNIQUES OF THE INSTRUCTIONAL STAFF OF THE COLLEGE OF CRIMINAL JUSTICE EDUCATION - GUADAMOR, MAITA (International Journal of Arts, Sciences and Education, 2021)
Abstract: As the college has shifted to online classes due to this pandemic, the criminology faculty members saw to it that the quality of teaching has not changed but rather became better with the use of different platforms, innovating techniques and strategies, with the provisions of more reading materials, video clips and case studies for studies to be more focused on their studies. This undertaking is intended to show the evaluation of students of the teaching behavioural attributes of the faculty members of the College of Criminal Justice Education of Piat Campus specifically on the teaching classroom management and evaluative techniques using the descriptive method of research. Respondents of the study were chosen through convenience sampling considering of the current situation. The descriptive statistics used to summarize the profile of the respondents were percentages, frequency counts and in the analysis and interpretation of the evaluation of the respondents as regards the teaching behavioural attributes of the faculty members, the weighted mean was used. With the conduct of this study, results have led to the conclusion that the evaluation of the respondents on the classroom management and the teaching and evaluative techniques of both the tenured and the non-tenured faculty members are very satisfactory. In the view of the findings of this study, the researchers recommend that regular classrooms observation of the faculty members by the department chairs or by the deans should be conducted so as to ensure the effective classroom management of the faculty and regular trainings and/or seminar may be initiated by the college to enrich the teaching strategies and evaluative techniques of the faculty members.